The Effect of Leadership, Work Environment and Motivation on Nurse Performance - Sitti Zubaedah; Joko Prasetyo (Jurnal Manajemen Bisnis, 2023)
This study aims to examine and analyze the influence of leadership, work environment and motivation on the performance of nurses at the Jayapura Papua Regional General Hospital. The population in this study were all nurses at the Jayapura Regional General Hospital, Papua, totaling 348. The technique used to determine the sample in this study was simple random sampling technique to measure the sample size to be studied. After doing calculations with the slovin formula, the number of samples used after being rounded up is 100 nurses. The data source for this research is primary data, namely data obtained from the results of distributing questionnaires to all respondents. The statistical method used to test the hypothesis is multiple linear regression analysis with the help of SPSS. The results of this study indicate that based on the partial test Leadership and motivation have a positive but not significant effect on Nurse Performance, while the work environment has a positive and significant effect on Nurse Performance and the results of the simultaneous test Leadership, Work Environment and Motivation simultaneously have a positive and significant effect on Nurse Performance.